Five-Strand Hamstring Autografts for Anterior Cruciate Ligament Reconstruction: A Systematic Review. Issue 2 (22nd February 2019) - Smith, John-Rudolph H.; Houck, Darby A.; Hart, Jessica A.; Vidal, Armando F.; Frank, Rachel M.; Bravman, Jonathan T.; McCarty, Eric C.
Background: Recent studies have described surgical techniques to increase the hamstring graft diameter for anterior cruciate ligament reconstruction (ACLR), particularly for 5-strand hamstring (5HS) autografts. Purpose: To review the literature examining the biomechanical and clinical outcomes of 5HS autografts for ACLR. Study Design: Systematic review; Level of evidence, 3. Methods: A systematic review using PRISMA (Preferred Reporting Items for Systematic Meta-Analyses) guidelines was performed by searching PubMed, Embase, and the Cochrane Library for studies reporting the biomechanical and clinical outcomes of 5HS autografts. All English-language literature published from 2012 to 2018 that reported the biomechanical properties of 5HS grafts and/or clinical outcomes after ACLR with 5HS autografts with a minimum 1-year follow-up was reviewed by 2 independent reviewers. Graft diameter, stiffness, displacement, strength, failure rates, anteroposterior knee laxity, and patient-reported outcome scores were collected. The study methodology was evaluated using the modified Coleman Methodology Score. Results: Two biomechanical and 3 clinical studies (1 with level 2 evidence, 2 with level 3 evidence) were included. The biomechanical studies compared the results of fourteen 4-strand hamstring (4HS) and fourteen 5HS graft specimens for ACLR (ovine grafts, n = 12; cadaveric grafts, n = 16) and found no significant differences in ultimate load, stiffness, displacement, and stress relaxation ( P > .05), likely attributed to insufficient incorporation of the fifth strand. The mean 5HS cadaveric graft diameter (8.2 mm) was significantly greater than that of 4HS grafts (6.8 mm) ( P = .002), whereas the mean ovine graft diameters were not significantly different (4HS, 5.2 mm; 5HS, 5.3 mm) ( P > .05). Two clinical studies compared the outcomes after ACLR of 53 patients with a 4HS autograft versus 62 patients with a 5HS autograft, while 1 clinical study reported the outcomes of 25 patients after ACLR with a 5HS autograft (mean age, 28.7 years; mean follow-up, 24.8 months). The overall mean diameter for 4HS and 5HS autografts was 8.4 and 9.1 mm, respectively. There was no significant difference in failure rates between 4HS and 5HS autografts ( P = .82). None of the comparative studies reported significant differences in any clinical outcomes ( P > .05 for all). Conclusion: The available literature on traditional 4HS and 5HS autografts for ACLR is limited. Of the available data, clinical and biomechanical studies suggest no difference in outcomes after ACLR with either graft construct. Additional research is needed to determine whether creating a 5HS graft is beneficial.